Green Vehicles and Public perception: A Southeast Asian Perspective - Abdul Kafi; Abdurrahman Faris Indriya Himawan; Lai Fatt Chuah; Mazhar Abbas; Nura Abubakar Allumi; Norlinda Mohd Rozar; Muhammad Ashlyzan Razik; Nur Hafiza Mr Muhamaruesa; Anuar Abu Bakar; Nizamuddin Zainuddin (Chemical Engineering Transactions)
Understanding public perception of eco-friendly transportation is critical for global climate change mitigation. This study investigates the factors influencing public perception of green vehicles in Malaysia and Thailand. A quantitative survey (n=140) targeting green vehicle and non-green vehicle owners in major cities of both countries was surveyed. Convenience sampling and regression analysis revealed a significant relationship between knowledge of green transportation, awareness of green transportation, green transportation costs and green transportation perception. These findings highlight the importance of addressing knowledge gaps and cost concerns to encourage green transportation adoption among Southeast Asian vehicle users. This information can guide policymakers and marketers in developing strategies to promote sustainable travel options. Future research could explore additional factors or expand geographically to gain a more comprehensive understanding.